PERAN PEMERINTAH DAERAH MELALUI CABANG DINAS PENDIDIKAN WILAYAH II DALAM MENANGANI KETERBATASAN SMA NEGERI DI KOTA DEPOK PROVINSI JAWA BARAT - Bilqis Anas Thalib; Fani Sahabi’ah; Ersa Falena Fitri; Zeicha Putri Rahmawanti (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze the role of the Depok City Government, specifically the Branch Office of the West Java Provincial Education Office II, in addressing the limitations of public high schools (SMA) in the city. The background of the issue raised is the imbalance between the number of students wishing to continue to SMA and the limited capacity of public schools, resulting in thousands of students being unable to be admitted to public SMA. This research uses a qualitative method with data collection techniques including interviews, observations, and documentation. The findings show that the government plays a role as a facilitator by providing adequate educational facilities, as a regulator by implementing zoning systems and affirmative action routes, and as a catalyst by encouraging the development of new schools and the implementation of hybrid learning methods. However, significant challenges remain related to the shortage of public schools, which cannot be fully addressed by only providing grants or scholarships. This study concludes that the addition of public high schools in Depok City and improvements in the zoning system are crucial to addressing the educational challenges.